2019
DOI: 10.1021/acs.jproteome.9b00338
|View full text |Cite
|
Sign up to set email alerts
|

Mapping Interactome Networks of DNAJC11, a Novel Mitochondrial Protein Causing Neuromuscular Pathology in Mice

Abstract: We previously identified DNAJC11, a mitochondrial outer membrane protein of unknown function, as a novel genetic cause in modeled neuromuscular disease. To understand the physiological role of DNAJC11, we employed a proteomic approach for the identification of the DNAJC11 interactome, through the expression of DNAJC11-FLAG in HEK293FT cells and transgenic mice. Our analysis confirmed known DNAJC11-interacting proteins including members of the MICOS complex that organize mitochondrial cristae formation. Moreove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 67 publications
0
10
0
Order By: Relevance
“…The reverse primer 5′-GCG GCC GCΤ ΑΑC TTA TCG TCG TCA TCC TTG TAA TCA ATG TTA TTT TGA AGA AG-3′ (Eurofins Scientific) contained a NotI site, the 24 bp FLAG sequence, and 18 bp of the 3′ SLC25A46 cDNA. The PCR product of 1301 bp was digested with the restriction enzymes HindIII and NotI (ThermoFisher Scientific) and subcloned between the CBX3/hnRNPA2 promoter (5.5 kb) and the 3′ human beta-globin sequence (2.8 kb) of a plasmid digested also with the HindIII and NotI enzymes . The recombinant plasmid transformed the Escherichia coli strain XL1-blue, and selected bacterial clones were sequenced (CeMIA SA) using the primers described above.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The reverse primer 5′-GCG GCC GCΤ ΑΑC TTA TCG TCG TCA TCC TTG TAA TCA ATG TTA TTT TGA AGA AG-3′ (Eurofins Scientific) contained a NotI site, the 24 bp FLAG sequence, and 18 bp of the 3′ SLC25A46 cDNA. The PCR product of 1301 bp was digested with the restriction enzymes HindIII and NotI (ThermoFisher Scientific) and subcloned between the CBX3/hnRNPA2 promoter (5.5 kb) and the 3′ human beta-globin sequence (2.8 kb) of a plasmid digested also with the HindIII and NotI enzymes . The recombinant plasmid transformed the Escherichia coli strain XL1-blue, and selected bacterial clones were sequenced (CeMIA SA) using the primers described above.…”
Section: Methodsmentioning
confidence: 99%
“…The samples were centrifuged and resuspended in Laemmli buffer (2% SDS, 10% glycerol, 1% 2-mercaptoethanol, 0.002% bromophenol blue, 0.125 mM Tris/HCl, pH 6.8). As a control, 50 μg of intact mitochondria was resuspended in 1% Triton X-100, centrifuged (12,000 g for 10 min at 4 °C), and treated with proteinase K …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the MICOS complex can directly or indirectly interact with other proteins and play a critical role in maintaining mitochondrial ultrastructure. For example, DNAJC11 helps to maintain proper cristae morphology by interacting with the peripheral MICOS complex ( Violitzi et al, 2019 ).…”
Section: Mitochondrial Dynamics In Skeletal Musclementioning
confidence: 99%
“…One of these being DNAJC11, which helps to maintain and uphold proper cristae morphology by interacting with the MICOS complex peripherally. However, the exact mechanism of interaction between DNAJC11 and MICOS or the mitochondrial intermembrane space bridging (MIB) complex, of which MICOS is a part and which is discussed further in detail later in this review, is poorly understood [54,[68][69][70]. Studies in mice have shown that a mutation in the DNAJC11 gene leads to abnormal cristae structures [71].…”
Section: Accepted Articlementioning
confidence: 99%